2019
DOI: 10.3389/fendo.2019.00231
|View full text |Cite
|
Sign up to set email alerts
|

Five Neuropeptide Ligands Meet One Receptor: How Does This Tally? A Structure-Activity Relationship Study Using Adipokinetic Bioassays With the Sphingid Moth, Hippotion eson

Abstract: Adipokinetic hormones (AKHs) play a major role in mobilizing stored energy metabolites during energetic demand in insects. We showed previously (i) the sphingid moth Hippotion eson synthesizes the highest number of AKHs ever recorded, viz. five, in its corpus cardiacum: two octa- (Hipes-AKH-I and II), two nona- (Hipes-AKH-III and Manse-AKH), and one decapeptide (Manse-AKH-II), which are all active in lipid mobilization ( 1 ). (ii) Lacol-AKH from a noctuid moth show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Similar observations have been made with AKH analogs tested using both in vivo and in vitro assays whereby complete removal of the N-terminal pyroglutamate abolishes activity of the AKH analog whereas the alternatively blocked N-terminus (i.e. N-Acetyl-Ala), or even simply glutamate or glutamine that can spontantenously undergo cyclization (Schilling et al, 2008), were shown to have improved activity, albeit lower than the native AKH (Caers et al, 2016; Gäde and Hayes, 1995; Marco and Gäde, 2019b). Lastly, although alanine substitution for valine in the second position led to a relatively minor effect on ACPR activation (~70-fold reduced activity), the internally truncated analog omitting valine within the N-terminal region elicited no activation of the ACPR, indicating the spacing between the more critical residues, namely pyroglutamate and polar threonine, is essential for ACP peptide activity on the ACPR.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar observations have been made with AKH analogs tested using both in vivo and in vitro assays whereby complete removal of the N-terminal pyroglutamate abolishes activity of the AKH analog whereas the alternatively blocked N-terminus (i.e. N-Acetyl-Ala), or even simply glutamate or glutamine that can spontantenously undergo cyclization (Schilling et al, 2008), were shown to have improved activity, albeit lower than the native AKH (Caers et al, 2016; Gäde and Hayes, 1995; Marco and Gäde, 2019b). Lastly, although alanine substitution for valine in the second position led to a relatively minor effect on ACPR activation (~70-fold reduced activity), the internally truncated analog omitting valine within the N-terminal region elicited no activation of the ACPR, indicating the spacing between the more critical residues, namely pyroglutamate and polar threonine, is essential for ACP peptide activity on the ACPR.…”
Section: Discussionsupporting
confidence: 68%
“…In light of the high fidelity of the three GnRH-related systems (Hansen et al, 2010; Oryan et al, 2018; Wahedi and Paluzzi, 2018), the current study set out to examine for the first time the ligand structure-activity relationship for an insect ACP receptor. This is of utmost importance in order to gain insight on the specific structural features of the ACP system given that extensive studies have been carried out previously on AKH receptors in a variety of species using natural and synthetic analogs of this neuropeptide family (Caers et al, 2012; Fox and Reynolds, 1991; Gäde et al, 2000; Gäde, 1992; Gäde, 1993; Gäde et al, 2016; Keeley et al, 1991; Lee and Goldsworthy, 1996; Lee et al, 1996; Lee et al, 1997; Marco and Gäde, 2015; Marco and Gäde, 2019b; Poulos et al, 1994; Velentza et al, 2000; Ziegler et al, 1991; Ziegler et al, 1998). By examining the activity of a variety of ACP analogs on the activation of the A. aegytpi ACP receptor (ACPR), including single alanine substitutions along with truncated or extended analogs, a few observations can be highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harax‐AKH in the Coccinelloidea and Trica‐AKH in the Tenebrionoidea (see Table ). Interestingly, the latter 2 peptides share the C‐terminal amidated tetrapeptide completely (STGW amide) or mostly (STDW amide) with the ancestral Schgr‐AKH‐II; a substitution at position 7 has previously not shown much difference in AKH receptor activation in vitro (Caers et al, ; Marco, Verlinden, Vanden Broeck, & Gäde, ; Marchal et al, ) or in vivo (Gäde & Hayes, ; Marco & Gäde, ).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo structure‐activity studies with P. americana to test the biological response to various naturally occurring AKHs (Gäde, ) and a series with single amino acid substitutions have been performed (Gäde & Hayes, ). These studies demonstrated that the AKH receptor of P. americana can bind a fair number of different AKHs, but this may be explained by the fact that more than one AKH peptide structure is produced and active in this species, while all evidence seems to indicate that insects have only one AKH receptor, regardless of the number of AKH structures produced (Marco & Gäde, ). In H. abietis on the other hand, in which Peram‐CAH‐I is the sole conspecific AKH, five other naturally occurring AKHs were tested in an in vitro system in which the receptor was expressed with a G protein, and none of the heterospecific ligands could attain 40% or higher activation of the receptor when applied in the nM range (Marchal et al, ).…”
Section: Resultsmentioning
confidence: 99%